Deteksi dan Identifikasi Telur Cacing Nematoda pada Feses Sapi Bali (Bos sondaicus) di Desa Mumbul Sari Kecamatan Bayan Kabupaten Lombok Utara - Mujmal, Khaerul; Dharmawibawa, Iwan Doddy; Kholik, Kholik; Janah, Maratun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Indonesia is a country rich in natural resources, including in the field of livestock, one of which is cattle. Cows have an important role as providers of meat needs for the community. However, cows are also at risk of being infected with worms that can reduce immunity, inhibit weight gain, and potentially cause death. The purpose of this study is to detect and identify nematode worm eggs in the feces of Balinese cows (Bos sondaicus) located in Mumbul Sari Village, North Lombok Regency. The sampling method in this study uses the purposive sampling method based on the maintenance system. Sampling of Balinese cow feces (Bos sondaicus) was taken in Mumbul Sari Village, North Lombok Regency, by taking fresh cow feces, then taken to the Parasitology Laboratory, Faculty of Veterinary Medicine, Mandalika Education University, to be examined using the saturated sugar flotation method, then observed under a microscope with a magnification of 100 times. The results of the study showed positive examination, namely the presence of Trichostrongylus sp; Toxocara vitulorum sp; Oesophagostomum sp; and Haemonchus contortus sp; on the feces of Balinese cattle from Mumbul Sari Hamlet, Bagek Nunggal, Pawang Kunyit I, Pawang Kunyit II, and Munder Hamlet.